Association between immune-related adverse events and prognosis in immune checkpoint inhibitor therapy: A bibliometric and visual analysis - Jun Zhao; Xianghua Quan; Yu Liang; Beibei Ni; Xiaomin Xing; Guangwei Liu (Human Vaccines & Immunotherapeutics)
With the gradual improvement in tumor immunotherapy, the incidence of immune-related adverse events (irAEs) has increased. However, according to current research, the relationship between irAEs and prognosis remains a contentious issue. This study used bibliometrics research to investigate hotspots and future trends on the relationship between irAEs and prognosis and to serve as a resource for researchers in this field. In the core literature database of Web of Science, the keywords immune checkpoint inhibitors(ICIs), immune-related adverse events, prognosis were used to search for the articles and reviews in the field of irAEs and prognosis. Set the time parameter to January 2007 to December 2023. Visualization analysis software CiteSpace 6.1.R6, VOSviewer1.6.18 and Carrots2 were used to conduct quantitative statistical and visual research on the author, institution, country, keyword, publication, cited literature, research status, research hotspots and development trends of the relevant research. The analytic research was based on original articles and reviews. 724 articles from 308 countries led by China(147)，the United States(131), and Japan(105) were included. The most popular tumor type is melanoma, small-cell lung cancer, and renal cell carcinoma. The focus topics in this field encompass “Myasthenia gravis,” “neurotoxicity,” “liver damage,” “head and neck adverse events,” “colitis,” and “skin adverse events.” This study has provided a valuable reference for future research in this field. Combination therapy, predictive biomarkers, patients’ preexisting conditions, glucocorticoids, prognostic indicators, ICI rechallenge, and other topics could become research hotspots which will help us to identify useful information from complex big data and provide a basis for precise medicine for immune checkpoint inhibitor therapy.